Active myofascial trigger points in head and neck muscles of patients with chronic tension-type headache in two primary health care units in Tshwane - K. Joseph (AOSIS, 2016)
Background: The management of patients presenting with chronic tension-type headache (CTTH) can be challenging for primary health care practitioners. As with most chronic pain disorders, a multimodal management approach is frequently required. It has been postulated that myofascial pain syndrome (MPS) and its hallmark myofascial trigger points (MTrPs) found in specific muscle tissues may play a role in the chronic pain experienced by patients with CTTH. Little is known about the prevalence of MTrPs in patients with CTTH, in primary health care settings on the African continent. This study therefore aimed to investigate the prevalence of active MTrP’s in specific head and neck muscles/muscle groups in patients with CTTH.